Notice of the Roman Altars, &c., presented by the Right Hon Sir George Clerk of Penicuik, Bart (Proceedings of the Society of Antiquaries of Scotland, 1862)
Sixteen Roman artefacts were presented to the Society by George Clark in December 1857 along with a list of where they were found. The article contains this list, a page with illustrations of some of the artefacts, and a short biography of the Sir John Clerk, the eighteenth-century antiquarian who collected the objects.